(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
Basketball is a complex coordination sport, and the sports result of the players is to some extent determined by the technical fitness. According to basketball coaches, the most effective way to improve the technical fitness of the players is to develop their coordination abilities. This is a manifestation of the ability to control their own motor actions. The effectiveness of the experimental program for the development of coordination abilities of basketball players was assessed by the results of repeated testing of athletes from the experimental group who trained according to the developed method and basketball players from the control group who trained according to the traditional method. To determine the impact of the results of the experiment on the technical fitness of basketball players, the results of their performances at competitions were analyzed. Repeated testing showed a significant improvement in the indicators of coordination abilities of basketball players from the experimental group compared to the control group. Thus, the average statistical result of the development of static balance in the experimental group was 85.0±5.5 s (an increase of 42.6%), and in the control group - only 63.3±2.1 s (an increase of 4.6%). The dynamic balance indicators of basketball players in the experimental group were 7.5±0.3 s (an increase of 13.8%), and in the control group - 8.4 s (an increase of 2.3%). The state of development of static-dynamic balance improved in athletes in the experimental group by 25.9%, and in basketball players in the control group, only by 4.2%. Thus, the effectiveness of the experimental program is confirmed by the increase in all studied results of coordination abilities of basketball players in the training group. According to the indicators of a significant number of tests, their increase is 3 times greater than in the control group (p<0.05 - 0.01). In addition, the results of performances at competitions of basketball players in the experimental group are better than in the control players (the percentage of hits from the game in the CG is 32, and in the EG is 40).